Peran perpustakaan sekolah dalam mendukung pembelajaran kolaboratif - Husaini, Rusdiana; Hajiri, Moch. Isra (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. Libraries, as centers of intellectual resources and information, have the potential to become environments that support collaborative learning. This research aims to describe the role of the school libraries in supporting collaborative learning. Data collection methods. This study was qualitative approach with a descriptive method. The research was conducted in three high school libraries in South Kalimantan Province, namely: School A, School B, and School C. Data collection was carried out through interviews, observations, and documentation. The collected data were subsequently analyzed using the interactive model by Miles and Huberman. Results and Discussion. School libraries currently contribute to collaborative learning by providing spaces and facilities for group work and activities. However, it showed the limited quantity of resources, including computers and internet bandwidth so no all students can leverage optimally. The space is equivalent to a classroom, however, it is inadequate for a larger audience. Conclusion and suggestions. The role of the school libraries in this research has not been optimal in facilitating and supporting collaborative learning in the schools. The library can make plans to address this gradually, particularly in terms of preparing supporting infrastructure.